Mozambique : Private Participation in Isolated Electrical Grids - Sakairi, Yuriko (World Bank, Washington, DC, 2012)
The note outlines the impacts of the Urban Household Energy Project in Mozambique, identifying cost-recovery tariffs, employment generation, and improved services, including the significant achievement of power sector reforms, which allowed the creation of independent grids. Following the passage of the Electricity Law in 1997, which de-monopolized the national power utility, and allowed private sector participation in the industry, the above mentioned project funded a pilot isolated grid electrification project in two coastal towns, which extended low-cost services to these isolated areas, after an enabling framework had been created for private participation.